Análisis del rendimiento y rentabilidad en pollos de engorde Cobb 500 con diferentes dietas en Zúngarococha, en el 2024 - Castillo Orellana, Oscar Eduardo (2025)
The study evaluates the impact of different commercial diets and a locally formulated diet on the performance and profitability of Cobb 500 broilers in Zúngarococha. This research arises from the need to optimize food resources in poultry farming, a key sector for the local and national economy, looking for food alternatives that maximize production at the lowest possible cost. The overall objective was to determine how different diets affect the performance in terms of weight, feed conversion and economic profitability of chickens. To do this, a completely randomized experimental design (DCA) was used with three dietary treatments (Corina, Broiler and own diet) and 40 replicates per treatment. Variables such as final weight, weight gain, feed intake, feed conversion and economic profitability were measured. The data collected were analyzed using ANOVA and Tukey's tests to identify significant differences between treatments. The results indicate that treatment with the Corina diet produced the highest final weight, followed by Broiler, while the own diet was the most economical and cost effective option. The Corina diet, while expensive, generated the highest gross receipts per chicken. In conclusion, each diet offers advantages according to the production objective: Corina maximizes gross income and final weight, while the own diet is the most profitable in relation to investment costs. Further research on locally formulated diets is recommended, due to their potential to improve the profitability of the poultry sector.